2007
DOI: 10.1177/0883073807305672
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Muscular Atrophy Genetic Counseling Access and Genetic Knowledge: Parents' Perspectives

Abstract: Spinal muscular atrophy is characterized by degeneration of α motor neurons in the anterior horns of the spinal cord, which leads to progressive symmetrical muscle weakness and atrophy. Spinal muscular atrophy is the leading fatal autosomal recessive disorder in infancy, and genetic counseling is an essential component of the care of families of these patients. However, little guidance is available in the published literature regarding the process and benefit of genetic counseling for families. Accordingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 11 publications
0
37
1
1
Order By: Relevance
“…[1][2][3][4]10,30 The finding that some parents persist with requests and receive testing is important because previous studies have not distinguished between carrier testing driven by parental requests and medical recommendations. 22,31,32 This study identified surprising differences in the reported frequency of parental requests for carrier testing in their children. The interview process uncovered variation in what counts as a request for testing, with one interpretation being that a simple expression of interest constitutes a request and another being that only a more formal and specific request for carrier testing does so.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4]10,30 The finding that some parents persist with requests and receive testing is important because previous studies have not distinguished between carrier testing driven by parental requests and medical recommendations. 22,31,32 This study identified surprising differences in the reported frequency of parental requests for carrier testing in their children. The interview process uncovered variation in what counts as a request for testing, with one interpretation being that a simple expression of interest constitutes a request and another being that only a more formal and specific request for carrier testing does so.…”
Section: Discussionmentioning
confidence: 91%
“…1 The disease is characterized by the progressive degeneration and loss of anterior horn cells in the spinal cord and brainstem nuclei causing symmetric muscle weakness and atrophy, 2,3 and the clinical subtypes (I-IV) are primarily based on age at onset and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…9,12 In some cases, carrier testing is carried out for the sibling of an affected child despite the recommendations. 1,[13][14][15][16][17][18][19] Studies reporting carrier-testing practices of health professionals indicate that genetic health professionals are willing to facilitate carrier testing for autosomal recessive and X-linked conditions in unaffected children to varying degrees. [13][14][15][16]20 For example, in an interview-based study of 17 key informant genetic health professionals in Australia, we found that all our participants initially recommended against carrier testing in children following parental requests, with some preemptively discussing it as a test they generally do not perform.…”
Section: Introductionmentioning
confidence: 99%